The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-33602-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast agent based small vessel imaging of human thyroid using motion corrected power Doppler imaging

Abstract: Singular value based spatiotemporal clutter filtering (SVD-STF) can significantly improve the sensitivity of blood flow imaging in small vessels without using contrast agents. However, despite effective clutter filtering, large physiological motion in thyroid imaging can impact coherent integration of the Doppler signal and degrade the visualization of the underlying vasculature. In this study, we hypothesize that motion correction of the clutter filtered Doppler ensemble, prior to the power Doppler estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 47 publications
(47 reference statements)
1
43
0
Order By: Relevance
“…Further, the signature of carotid pulsation was visible in the lateral displacement estimates (a), which was expected given the anatomical orientation of the thyroid relative to carotid artery. These observations were similar to our previous report on feasibility of motion correction in thyroid nodules 14,34 . Lateral motion of the thyroid lesion was noticeably higher in the longitudinal view, compared to transverse.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Further, the signature of carotid pulsation was visible in the lateral displacement estimates (a), which was expected given the anatomical orientation of the thyroid relative to carotid artery. These observations were similar to our previous report on feasibility of motion correction in thyroid nodules 14,34 . Lateral motion of the thyroid lesion was noticeably higher in the longitudinal view, compared to transverse.…”
Section: Resultssupporting
confidence: 93%
“…To address the second issue of incoherent Doppler integration, we demonstrated that motion correction could substantially improve the performance of Doppler imaging of thyroid blood vessels [ Fig. 1(c,d)] 14 . Specifically, thyroid motion was estimated as components of axial and lateral displacements using 2D normalized cross-correlation based speckle tracking of the Doppler ensemble, prior to clutter filtering.…”
mentioning
confidence: 99%
See 3 more Smart Citations